THE MAIN ISSUES OF GROUP MOTIVATION IN MODERN MANAGEMENT PSYCHOLOGY - Abdukarimov M. M. (Web of Journals Publishing, 2024)
This article presents valuable ideas about the main problems of group motivation in management psychology and modern approaches to the problem.
Keywords: management, psychology, group, group motivation, creative approach to the problem, labor relations.